Articulating the Identity of Characters with Bipolar Disorder in Silver Linings Playbook, Touched with Fire, dan The Other Half - Dite Nursyamsi Mahmutami (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
The representation of bipolar disorder in popular culture can become a reflection of society’s views toward the individuals with bipolar disorders. In this regard, the idea of a character with a bipolar disorder does not only emerge based on the situations in real life but also how people view them. Thus, the idea of an individual with bipolar disorder as a strange, dangerous, unstable, and irrational character might become a stereotype that emerges from the representation of mental disorder characters in popular media. This research aims to analyze identity articulation of mental disorder characters in films such as titled Silver Linings Playbook (2012), Touched with Fire (2015) and The Other Half (2016) and the discourse surrounding it using theories of representation and identity articulation. Using a qualitative research design, this research explores narrative elements, visuals, and social interactions of characters to understand how mental illness characters are constructed. The findings suggest that characters' identities are articulated through their struggles with stereotypes, interpersonal support, and a negotiation between individuality and social pressures. The result shows that although the three films successfully provide a more humane view of mental illness, they are still articulated with mental illness identities in mental illness discourse, reinforcing certain stereotypes.